The protective role of N-Acetyl Cysteine and vitamin C against atrazine-Induced Dopaminergic Neurodegeneration in N27 Cells - Sabah Hassain Enayah; Ahmed k. Al Atya; Afrah A. Maktoof (University of Thi-Qar Journal of Science, 2019)
Background: Atrazine (ATZ)has been associated with its capability to interact and damage DNA in neuronal cells. However, the molecular mechanisms of ATZ are not fully understood. In vitro and In vivo studies indicated that atrazine induces cytotoxicity and oxidative stress in human and animals. This study sought to determine the role of two antioxidants against the toxic impact of atrazine. Main Methods: N27 cell line pretreated to N-acetyl Cysteine NAC or Ascorbic acid AA alone or in combination before 24h atrazine exposure. Multiple intercellular antioxidant parameters measured such as (GSH, GSSG, MDA). Genotoxicity represented by single gel electrophoreses assay (comet assay). Results: the outcomes of this work demonstrated that higher protection against atrazine exposure at combination of NAC and AA comparing to the single exposure to each. The antioxidant acted in synergistic way to rescue cells from reactive oxygen species generated from atrazine exposure. DNA breaking or damage also prepared in better way in combination exposure comparing to the single exposure. Conclusion: the evidence of atrazine increase the oxidative damage have been approved by enhancing defense system to increase cell availability and DNA repair. While antioxidant (NAC&AA) prevent oxidative damage that causes by atrazine via increase cell viabilities and DNA fix.